2008
DOI: 10.1111/j.1469-7998.2007.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and adaptive diversity of rodents of the family Ctenomyidae (Caviomorpha): delimiting lineages and genera in the fossil record

Abstract: Differentiation of genera of the modern (Late Miocene to Recent) South American rodent family Ctenomyidae would have been linked to the acquisition of disparate adaptations to digging and life underground. In accordance with this hypothesis, the delimitation of lineages and genera in the ctenomyid fossil record is evaluated here following an adaptation-rooted criterion that involves both an assessment of the monophyly and of the adaptive profiles of recognized clades. The application of such a criterion, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
23

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 35 publications
(48 reference statements)
1
77
0
23
Order By: Relevance
“…Deposits of the Monte Hermoso Formation in its type locality Farola Monte Hermoso were accumulated in a dynamic fluvial environment of high-sinuosity rivers ("muddy fine-grained rivers" in Miall, 1985). In these localities, none of the species of Xenodontomys has been recorded, being instead abundant Actenomys priscus, the most derived representative of the lineage Xenodontomys-Actenomys (Verzi, 2008). In addition, when these specimens are compared to specimens of A. priscus found in levels assigned to the Chapadmalalan (from the area of Mar del Plata-Miramar), the latter display a more derived dental morphology (Deschamps, 2003;Tomassini et al, 2013a).…”
Section: Systematic Biochronostratigraphic and Paleoenvironmental Comentioning
confidence: 99%
See 1 more Smart Citation
“…Deposits of the Monte Hermoso Formation in its type locality Farola Monte Hermoso were accumulated in a dynamic fluvial environment of high-sinuosity rivers ("muddy fine-grained rivers" in Miall, 1985). In these localities, none of the species of Xenodontomys has been recorded, being instead abundant Actenomys priscus, the most derived representative of the lineage Xenodontomys-Actenomys (Verzi, 2008). In addition, when these specimens are compared to specimens of A. priscus found in levels assigned to the Chapadmalalan (from the area of Mar del Plata-Miramar), the latter display a more derived dental morphology (Deschamps, 2003;Tomassini et al, 2013a).…”
Section: Systematic Biochronostratigraphic and Paleoenvironmental Comentioning
confidence: 99%
“…The first results were limited to specific localities (e.g., Quattrocchio et al, 1988;Deschamps and Borromei, 1992;Deschamps and Tonni, 1992;Verzi and Deschamps, 1996;Deschamps et al, 1998), but with time, data were used to make bio-chronostratigraphic proposals (Deschamps, 2003(Deschamps, , 2005, which were refined in subsequent papers (e.g., Verzi et al, 2004aVerzi et al, , 2008Deschamps et al, 2012Deschamps et al, , 2013Tomassini, 2012;Tomassini and Montalvo, 2013;Tomassini et al, 2013a) even making inferences about environmental conditions suggested by the recorded taxa. In this sense, rodents were particularly important among mammals (Verzi et al, 2004a;Quattrocchio et al, 2008;Deschamps et al, 2009Deschamps et al, , 2012Deschamps et al, , 2013Tomassini et al, 2013a;Vucetich et al, 2014aVucetich et al, ,b, 2015.…”
mentioning
confidence: 99%
“…В конце плиоцена они демонстрируют отчетливое уве-личение разнообразия, за которым следует вымирание всех родов за исключением рода Ctenomys. В плейстоцене наблюдается интенсивный кладогенез и значительная диверсификация тукотуко Verzi, 2008;Verzi et al, 2010).…”
Section: эволюционная история и современная дивергенция рода Ctenomysunclassified
“…Body size variation within the genus was most likely the result of selection pressures associated with the different habitats occupied by the approximately 56 living species [Vleck, 1979;Medina et al, 2007]. A distinctive characteristic of Ctenomys is that this genus has experienced an 'explosive' and relatively recent cladogenesis [Reig et al, 1990;Lessa and Cook, 1998;Verzi, 2008], posing the question of how brain size evolution tracked changes in body size. It was argued [Lande, 1979; see also Harvey and Bennett, 1983] that because direct selection on body weight does not seem to result in significant changes in brain weight, if closely related species are different mostly because of body size -for instance Ctenomys -their brain/body scaling coefficients would be expected to be lower than for species that are more distantly related, i.e., species within Caviomorpha in the present study.…”
mentioning
confidence: 99%
“…This process, which took place during the Pleistocene, yielded more than 10 fossil species and at least 56 living species [Reig et al, 1990;Verzi, 2008]. Subterranean rodents such as Ctenomys have been described as those species that live in underground burrows and conduct the vast majority of their life underground [Lacey et al, 2000].…”
mentioning
confidence: 99%